Organization of Effective Use of Islamic Financing Opportunities in Uzbekistan: Problems and their Solutions - Saydirasulov Laziz Alimovich (Scientific Trends, 2024)
Based on the selection and implementation of the Islamic finance model acceptable for the conditions of development of the new Uzbekistan, the necessity and relevance of ensuring the effective use of Islamic financing opportunities for various projects are substantiated. The problems that have arisen in this situation have been identified. The following are given: a method of systematic research and evaluation of the level of effective use of financing opportunities for various projects in non-Islamic countries based on the rules of the five Islamic sects (Sharia school); ways to effectively use the opportunities of Islamic financing in the implementation of various projects in the conditions of the development of new Uzbekistan.
Keywords: Islamic financing, non-Islamic states, sects, dualistic model, macro regulator.